Implementasi Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi dalam Digitalisasi Perpajakan di Indonesia - Mauliza Amigia Primayudhana (Universitas Wahid Hasyim, 2025)
The digitalization of taxation in Indonesia has brought significant changes to tax administration and introduced new challenges, particularly concerning the protection of taxpayers’ personal data. Following the enactment of Law Number 27 of 2022 on Personal Data Protection (PDP Law), the government is obligated to ensure that the digitalization of taxation is managed in accordance with existing regulations. This study aims to analyze the implementation of the PDP Law within Indonesia’s taxation system, as well as identify emerging obstacles and potential efforts to address them. This research employs a normative juridical method by examining regulations related to personal data protection and digital taxation, and by analyzing the challenges encountered in the implementation of data protection policies in the tax sector. The findings reveal that the implementation of the PDP Law in the digital taxation system faces various obstacles, including regulatory overlaps between taxation policies and personal data protection, inadequate technological infrastructure, and low taxpayer awareness of their data protection rights. Risks of data breaches and cyberattacks on digital taxation systems also pose major challenges. Therefore, more specific regulations concerning data protection in digital taxation systems are needed, alongside strengthened technological infrastructure for taxpayer data management and increased public outreach and education regarding personal data protection. These measures are expected to enhance security, transparency, and public trust in Indonesia’s taxation system.